The Effect of The Flipped Classroom Strategy on Science Achievement Among Fifth-Grade Primary School Students (Journal of the College of Basic Education, 2025)
The research aimed to identify “the effect of the flipped classroom strategy on the achievement of science subject among fifth-grade primary school students.” To verify the aim of the research, the researcher formulated the following null hypothesis: There is no statistically significant difference at the function level (0.05) between the average grades of the students in the experimental group who study according to the flipped classroom strategy, and the average grades of the students in the control group who study in the usual way in science.” The researcher adopted an experimental design with partial control and post-testing for the two research groups. The research sample consisted of (69) female students who were chosen randomly and were distributed into two groups: the experimental and the control groups. The researcher rewarded the female students of the two groups with the variables (chronological age, intelligence, and previous information test). Then I prepared an achievement test consisting of (40) objective multiple-choice items and confirmed the psychometric properties. After applying the test, the data was collected and processed statistically using a t-test for the two research samples, and it reached (2,821), which is greater than the tabulated value of (2). The results showed that there was a statistically significant difference at the function level (0.05) between the students of the experimental group who studied according to The flipped classroom strategy and the control group who studied according to the usual method in the post-achievement test in favor of the experimental group. In light of the research results, the researcher came up with a set of recommendations, including adopting the flipped classroom strategy in teaching science for the fifth grade of primary school and for all levels, and conducting similar studies with other variables and for other levels of study.